2003
DOI: 10.1161/01.atv.0000081740.65173.d1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Reduces VEGF-Induced Endothelial Adhesion Molecules and Adhesiveness Through a Phosphatidylinositol 3′-Kinase Pathway

Abstract: Objective-In the initial phase of inflammation, vascular endothelial growth factor (VEGF) can act as a proinflammatory cytokine by inducing adhesion molecules that bind leukocytes to endothelial cells. Adrenomedullin (AM) is known to act as either a proinflammatory or an anti-inflammatory agent. In this study, we examined the effects of AM on adhesion molecule expression and leukocyte adhesiveness in VEGF-stimulated human umbilical vein endothelial cells. Methods and Results-When stimulated with VEGF, the mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…We found that the expression of endothelial adhesion molecules and the subsequent accumulation of leukocytes in the vascular wall were attenuated in induced EC-Akt Tg mice. These results are consistent with a previous study showing that activation of Akt suppresses adhesion molecule expression in vitro (46). The increased production of NO by the Akt induction probably plays an important role in the suppression of inflammatory changes, since NO negatively regulates the expression of adhesion molecules (27,47).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the expression of endothelial adhesion molecules and the subsequent accumulation of leukocytes in the vascular wall were attenuated in induced EC-Akt Tg mice. These results are consistent with a previous study showing that activation of Akt suppresses adhesion molecule expression in vitro (46). The increased production of NO by the Akt induction probably plays an important role in the suppression of inflammatory changes, since NO negatively regulates the expression of adhesion molecules (27,47).…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, treatment with VEGF has been shown to induce adhesion molecules (E-Selectin, VCAM-1 and ICAM-1) in HUVECs(63-65) via an NFKBmediated process. E-Selectin has been shovm to be upregulated by VEGF treatment (66) or in response to inflammation (67,68), and plays an important role in tube formation as well as angiogenesis. E-Selectin also plays a major role in the adhesion of epithelial cancer cells to the endothelium (69).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Early growth response factor 1 (EGRl), SCYA2 (MCP-1), E-Selectin and VCAM-1 are all up-regulated in HUVECs (78,79), and all of these genes are induced by VEGFi2i/rGel treatment. Several members of the small inducible cytokine (SCYA) family of proteins were also over-expressed as a result of VEGFm/rGel treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that AM inhibited the proinflammatory effects of VEGF such as the induction of the expression of intercellular adhesion molecule-1, vascular cell adhesion molecule-1 and E-selectin. 22 Therefore, AM might cooperate with VEGF to stimulate proliferation and migration of VECs without inducing inflammation in the tissues. Our results support our hypothesis that an artery stenting model is required to analyze the mechanisms of coronary restenosis and explore strategies for the treatment of coronary restenosis.…”
Section: Am Stimulated Reendothelialization and Inhibited Neointimal mentioning
confidence: 99%